2018
DOI: 10.1080/1751696x.2018.1505815
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological and phenomenological transitions into how humans conceptualize and experience time

Abstract: Cosmographies associated with Western cosmologies demonstrate transformations from classic wheels of time and chains of being to scales of nature, chronologies, and pedigrees. Pedigrees in turn are converted into linear timelines, bifurcating trees, and multidirectional networks. These diagrammatical transitions associate with changes in how time is conceptualizedas circular, linear, multilinear, multidirectional, and perhaps as non-existent. This paper focuses on delineating the phenomenologies associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…How the four cosmologies understand causality correlates strongly with how they conceptually and diagrammatically understand and depict time (Gontier, 2016(Gontier, , 2018b. Ancient cultures developed cyclic time notions by studying planetary motions and life cycles.…”
Section: Correlations Between Time and Causality Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…How the four cosmologies understand causality correlates strongly with how they conceptually and diagrammatically understand and depict time (Gontier, 2016(Gontier, , 2018b. Ancient cultures developed cyclic time notions by studying planetary motions and life cycles.…”
Section: Correlations Between Time and Causality Thinkingmentioning
confidence: 99%
“…In hindsight, scholars can point toward diverse and multiple mechanisms and processes that underlie this diversification, but they often find it difficult to predict the future from the present. Scholars nowadays also question the uniformity of time In sum, Western cosmologies can be studied for how they differentially understand causality, and how this correlates with varying phenomenologies of time (Gontier, 2018b). The following sections exemplify the transitions here listed.…”
Section: Correlations Between Time and Causality Thinkingmentioning
confidence: 99%
“…Applied Evolutionary Epistemology (Gontier 2010;2017;2018c) is a philosophical theory and a scientific methodology that aims to identify and study the ontological structures foundational for biological, sociocultural, linguistic, and technological evolution and theorizing thereof. To that end, it analyzes how a plurality of units, levels, mechanisms and processes causally bring forth hierarchically-structured evolving realities that display diverging and converging patterns in the mode and tempo of their evolution.…”
Section: Three Schools With a Shared Agendamentioning
confidence: 99%
“…Concerning the evolution of epistemology, applied EE (Gontier 2018c) has come to reject the idea that there is a single reality or a world as it is in itself. Thinking through the consequences of traditional EE that already synthesized organisms with epistemology, as well as the consequences of cognitive and environmental niche construction theory that founded non-adaptationist EE, and by integrating the important insights coming in from the new evolutionary sciences, Gontier (2018c) has demonstrated that the epistemology-ontology divide has become untenable. Rather than adhering to the existence of an abiotic world in itself that somehow dissociates from a biotic world, applied EE understands organisms as constructors of spatiotemporally-bounded biorealities (Gontier & Bradie 2017).…”
Section: Three Schools With a Shared Agendamentioning
confidence: 99%
See 1 more Smart Citation